Ontophany and transimmanence in the experience of contemporary media artworks. Issue 3 (1st October 2019) - Freitas, Gabriela
AbstractHow have contemporary media artworks been proposing hybrid experiences, discussing the ontological implications from the experimentation with emerging techniques that alter our way of being-in-the-world? These experiences dialectically articulate aesthetic relations between real and virtual, visible and invisible, human and technological. In this article, we develop a participant observation of two specific works: Generation 244 (2011), by Scott Draves, and Zee (2008), by Kurt Hentschläger. This observation establishes a dialogue with phenomenology as it considers experience and perception as needed prerequisites for the analysis, as proposed by Merleau-Ponty. In this scenario, we have observed that a whole way of partitioning the sensible resets itself and points in the direction of a trans-immanence, generating an integrated knowledge that not only relies on reason, but in a collective wisdom where we can find, according to Didi-Huberman, a 'light of survival'.